Antiretroviral therapy reduces neurodegeneration in HIV infection. (28th January 2015) - Bryant, Alex K.; Ellis, Ronald J.; Umlauf, Anya; Gouaux, Ben; Soontornniyomkij, Virawudh; Letendre, Scott L.; Achim, Cristian L.; Masliah, Eliezer; Grant, Igor; Moore, David J.
<x xml:space="preserve">Abstract</x> Objective: To determine the effect of virally suppressive antiretroviral therapy (ART) on cortical neurodegeneration and associated neurocognitive impairment. Design: Retrospective, postmortem observational study. Methods: Clinical neuropsychological and postmortem neuropathology data were analyzed in 90 HIV-infected volunteers from the general community who had never undergone ART (n = 7, 'naive') or who had undergone ART and whose plasma viral load was detectable (n = 64 'unsuppressed') or undetectable (n = 19, 'suppressed') at the last clinical visit before death. Individuals were predominately men (74/90, 82%) with a mean age of 44.7 years (SD 9.8). Cortical neurodegeneration was quantified by measuring microtubule-associated protein (MAP2) and synaptophysin (SYP) density in midfrontal cortex tissue sections. Results: The suppressed group had higher SYP density than the naive group (P = 0.007) and higher MAP2 density than the unsuppressed group (P = 0.04). The suppressed group had lower odds of HIV-associated neurocognitive disorders than naive [odds ratio (OR) 0.07, P = 0.03]. Higher SYP was associated with lower likelihood of HIV-associated neurocognitive disorders in univariable (OR 0.8, P = 0.03) and multivariable models after controlling for ART and brain HIV p24 protein levels (OR 0.72, P = 0.01). Conclusion: We conclude that virally suppressive ART protects against cortical neurodegeneration. Further, we find evidence supporting the causal chain from treatment-mediated peripheral and central nervous system viral load suppression to reduced neurodegeneration and improved neurocognitive outcomes.